In situ direct growth of graphene/hexagonal boron nitride heterostructure on SiO2 substrate without metal catalyst. (November 2018) - Wu, Qinke; Lee, Joohyun; Sun, Jia; Song, Young Jae
Abstract: Here, we report the in situ direct growth of a graphene/hexagonal boron nitride (hBN) heterostructure on a SiO2 substrate without a metal catalyst by chemical vapor deposition (CVD). The hBN could be grown easily on a SiO2 substrate, while graphene growth was difficult and time-consuming as graphite could be grown only partially on the dielectric substrate, even after 5 h. Graphene was grown directly on this hBN/SiO2 substrate sequentially, which demonstrated easy and quick growth of a fully covered and high-quality graphene multilayer film within 40 min. The effect of hydrogen on the direct growth of hBN on a SiO2 substrate was also studied, and it was found that when a higher flow rate of hydrogen was used, the domain size was larger and higher quality of hBN could be grown. The quality of the grown hBN and graphene/hBN samples were confirmed by UV–vis, Raman, and atomic force microscopy (AFM). This new method can be used for graphene multilayer coating on dielectric substrates, on which it is difficult to grow graphene directly, for industrial or scientific applications. Graphical abstract: Image 1